The Effects of Resilience Training on the Self-Efficacy of Patients with Type 2 Diabetes: A Randomized Controlled Clinical Trial - Camellia Torabizadeh; Zahra ASadabadi poor; Maryam Shaygan (International Journal of Community Based Nursing and Midwifery, 2019)
Background: In view of the effect of self-efficacy on empowerment of patients and the role of resilience in the psychological adjustment and physical health of patients, the present study was conducted to examine the effect of resilience training on the self-efficacy of patients with type 2 diabetes. Methods: This double-blinded controlled clinical trial was carried out on 143 diabetic patients in the diabetes clinic in Shiraz between June 2016 and January 2017. Patients were selected using a simple sampling method and randomly divided into control (n=71) and intervention (n=72) groups. The intervention group received 6 sessions of training workshops on resilience skills. The control group received the routine educational pamphlets. The subjects completed diabetes self-efficacy questionnaire before, immediately after, and one month after completion of the intervention. Data were analyzed using SPSS version 16.0. Repeated measure ANOVA, t-test, and Chi-Square tests were used. PResults: Based on the results of the repeated measures ANOVAs, the overall score of self-efficacy was found to be significantly increased in the intervention group. Compared with the control group, the intervention group reported significantly higher levels of self-efficacy immediately after the intervention (P<0.001) and one month later (P<0.001). Conclusion: Training programs in resilience skills improves the self-efficacy of patients with type 2 diabetes. The results of this study support the use of resilience training in diabetics; it provides the health professionals and policymakers with an increased understanding of how to recognize the resilience skills for the improvement of self-efficacy. Trial Registration Number: IRCT2016022726790N1